Determinan Penentu Pertumbuhan Ekonomi di Jawa Timur - Hanadia Zahra; Prayudi S. Prabowo (Universitas Negeri Surabaya, 2026)
Economic growth in East Java experienced significant fluctuations during the 2019-2023 period, primarily due to the COVID-19 pandemic, which demands a deep understanding of the determinants of regional economic growth. This study aims to analyze the influence of District/City Minimum Wage (UMK), Human Development Index (IPM), and Labor Force Participation Rate (TPAK) on economic growth in 38 districts/cities of East Java. The method used is panel data regression with a Fixed Effect Model (FEM) approach on 2019-2023 data obtained from the Central Statistics Agency of East Java. The results show that UMK has a negative and significant effect on economic growth, while IPM has a positive and significant effect. However, TPAK shows no significant effect. Simultaneously, the three variables have a significant effect on economic growth with IPM acting as a key factor moderating this relationship. The conclusion of this study confirms the Endogenous Growth Theory and provides important policy implications for local governments in designing integrated development strategies between wage policies, improving human resource quality, and creating productive employment.